American Democracy, World Peace and the China Model—A Critical Analysis of Francis Fukuyama's "At the 'End of History' Still Stands Democracy". Issue 1 (2nd January 2016) - Enfu, Cheng; Chang'an, Xie
ABSTRACT: In "At the 'End of History' Still Stands Democracy, " Francis Fukuyama proposes that there has been no serious threat to his idea that Western style democracy is the "end of history" and that the United States does not damage global stability. Through analyzing and criticizing the main ideas of Francis Fukuyama, the conclusion is drawn that the China model is a powerful proof against his view of the "end of history." The tension in European and Asian regions is due to the instigation of the United States who in the 20 years since the end of the Cold War has wantonly launched wars under the excuse that human rights enjoy priority over sovereignty. Besides, a series of financial and economic crises in the Western world expose a set of disadvantages of capitalism, showing that human history has not ended up with the Western capitalist political system.